1953
DOI: 10.1149/1.2781135
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Formation of Coatings on Magnesium, Zinc, and Cadmium

Abstract: A report is given of recent investigations of anodically formed coatings on magnesium, zinc, and cadmium in normalNaOH and Na2CO3 solutions. The growth of the coatings was followed by means of x‐ray and electron diffraction and electron microscopy. It was found that the metal oxide was favored as initial product. Depending upon the relative magnitude of the solubility products, the coatings remained in the form of oxides or were converted into the respective hydroxides or carbonates. The semiconductance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 0 publications
7
77
0
1
Order By: Relevance
“…[5] He showed the relationship between the applied voltage and the characteristics of a film formed on Mg in 1 M NaOH. At voltages up to 3 V, the current density remained low, and a light grey protective film of Mg(OH) 2 was formed.…”
Section: Film Formation -Anodizing Behaviourmentioning
confidence: 99%
“…[5] He showed the relationship between the applied voltage and the characteristics of a film formed on Mg in 1 M NaOH. At voltages up to 3 V, the current density remained low, and a light grey protective film of Mg(OH) 2 was formed.…”
Section: Film Formation -Anodizing Behaviourmentioning
confidence: 99%
“…Some fundamental studies about the anodic behavior of Mg in alkaline solution have been published by Huber [18] and by Yahalom [19]. Recently, Cai et al [20] reported the formation of MgO coating films on magnesium in 6 M KOH solution by an anodic electrodeposition process, an alternative anodization of plasma oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The anodizing of magnesium in a wide range of potentials was first described in the works of Evangelides [1] and Huber [2]. Since that time, the formation of anodic coatings provided elaboration of some commercial anodizing processes, such as HAE and DOW17, etc.…”
Section: Introductionmentioning
confidence: 99%